Identification of a new quaternary association for legume lectins - Mendes Batista Moreno, Frederico Bruno [UNESP]; de Oliveira, Taiana Maia; Martil, Daiana Evelin [UNESP]; Vicoti, Magno Massolino [UNESP]; Bezerra, Gustavo Arruda; Beltran Abrego, Jose Ramon [UNESP]; Cavada, Benildo Sousa; de Azevedo, Walter FilgueIra (Academic Press Inc. Elsevier B.V., 2008)
Lotus tetragonolobus lectin (LTA) is a fucose-specific legume lectin. Although several studies report a diverse combination of biological activities for LTA, little is known about the mechanisms involved in L-fucosyl oligosaccharide recognition. The crystal structure of LTA at 2.0 angstrom resolution reveals a different legume lectin tetramer. Its structure consists of a homotetramer composed of two back-to-back GS4-like dimers arranged in a new mode, resulting in a novel tetramer. The LTA N-linked carbohydrate at Asn4 and the unusual LTA dimer-dimer interaction are related to its particular mode of tetramerization. In addition, we used small angle X-ray scattering to investigate the quaternary structure of LTA in solution and to compare it to the crystalline structure. Although the crystal structure of LTA has revealed a conserved metal-binding site, its L-fucose-binding site presents some punctual differences. Our investigation of the new tetramer of LTA and its fucose-binding site is essential for further studies related to cross-linking between LTA and complex divalent L-fucosyl carbohydrates. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Lotus tetragonolobus lectin (LTA); crystal structure; L-fucosyl